2022
DOI: 10.3390/su14116730
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rural Areas in Ukraine in the Context of Decentralization: An Empirical Study

Abstract: Decentralization in Ukraine was actualized due to the inability of the local self-government system to satisfy the needs of the rural population in public services for the comprehensive development of a person, their self-realization, and the protection of their constitutional rights. The purpose of this empirical study is to examine development of rural areas in Ukraine in the context of decentralization. The methodology used was exploratory qualitative in nature and used a multiple case study, wherein data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…They are recognized in many European countries, as well: stadtbezirk (Germany), parish (Spain), freguesia (Portugal), sołectwo (Poland), synoikia (Greece), kmetstvo (Bulgaria), kmetij (Slovenia), concejos, pedanías or parroquias (Spain), autonomous villages (Turkey), little town-halls (Czech Republic), neighborhoods, etc. [10,[45][46][47][48][49][50]. They have been seen as identity-and community-keeping institutions or tools with which to facilitate the implementation of service delivery and mitigate the adverse effects of amalgamation reforms.…”
Section: Overview Of Territorial Decentralization In Serbia 21 Territ...mentioning
confidence: 99%
See 3 more Smart Citations
“…They are recognized in many European countries, as well: stadtbezirk (Germany), parish (Spain), freguesia (Portugal), sołectwo (Poland), synoikia (Greece), kmetstvo (Bulgaria), kmetij (Slovenia), concejos, pedanías or parroquias (Spain), autonomous villages (Turkey), little town-halls (Czech Republic), neighborhoods, etc. [10,[45][46][47][48][49][50]. They have been seen as identity-and community-keeping institutions or tools with which to facilitate the implementation of service delivery and mitigate the adverse effects of amalgamation reforms.…”
Section: Overview Of Territorial Decentralization In Serbia 21 Territ...mentioning
confidence: 99%
“…As various empirical studies have shown, decentralization, as a process, and its effects could be different depending on the level of development achieved. In high-income countries, decentralization led to a reduction of regional inequalities, while in low-and medium-income countries, fiscal decentralization has led to significant regional disparities [9,10]. Through decentralization, developing countries can improve the distribution of income and rural areas' development [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al (2022) analyzed that the digital economy has a positive effect on quality regional development and strengthening of the state's financial and economic security system. In addition, the problem of managing the system of financial and economic security of the state for a long time has been causing active discussions among researchers regarding the feasibility of applying certain methodological approaches to the management of the financial security system (Davydenko et al, 2022), the features of the introduction of a systemic-behavioral approach to the system of guaranteeing the financial security of economic systems (Leliuk, 2015), specific aspects of monitoring and assessing the state of financial security of the state ( Sirenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%